If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2 + -1x = 2(x + 3) Reorder the terms: 2 + 5x + -1x = 2(x + 3) Combine like terms: 5x + -1x = 4x 2 + 4x = 2(x + 3) Reorder the terms: 2 + 4x = 2(3 + x) 2 + 4x = (3 * 2 + x * 2) 2 + 4x = (6 + 2x) Solving 2 + 4x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + 4x + -2x = 6 + 2x + -2x Combine like terms: 4x + -2x = 2x 2 + 2x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + 2x = 6 + 0 2 + 2x = 6 Add '-2' to each side of the equation. 2 + -2 + 2x = 6 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 6 + -2 2x = 6 + -2 Combine like terms: 6 + -2 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| 5(3x+2)-4+2(-5x+4)-3+14+2(5x-1)-7(3x+2y)+5(4x+2y)+11(5x+3y)+4(12x+5y)= | | 28=(4+x)+x | | 178-5x=40x+18 | | 9-x=x | | 2(x-4)+4x=10 | | -x+-3=7 | | .75v-6=.75v-6 | | 2x2=3 | | 6(c+9)=5c-1 | | 4=0.33(b+2) | | 7(x-1)+5=6-8x+7 | | 5x+3x=7x+2 | | 9x-5=3x-59 | | 21+2=24 | | 6x+9y=72 | | 4(y-9)=(y+21) | | 5(x-6)=9(2x+1) | | 6x+9=4x+13 | | 4x-(2x-3)=14 | | 0.6(x+100)+0.4x=85 | | 4s+2s-6=6 | | 7x+18=-2(x-18) | | -11/20=x-13/16 | | -11=14+x | | 4x+3=22x | | 2x-13=8-6x+3 | | 2(4x+3)=5(3x+4) | | x(5x+21)+18=0 | | 5p-100=x | | 84-7x=11x+20 | | 2(5x+8)=3(4x-2) | | 2x+19=9x-44 |